Patterns of Religious Coping among Bereaved College Students - Lord, Benjamin D. (Journal of religion and health, 2014)
Contemporary research has suggested that bereavement is a paramount issue in college populations, a group which has historically been underrepresented in grief research (Balk. in Death studies 25:67-84, 2001; Balk et al. in Death Studies 34:459-468, 2010). Indeed, there has been a call to generate new research on grief with specific populations and age groups (Center for the Advancement of Health. in Death Studies 28:568-575, 2004). Religion is often described as a primary way that individuals cope with bereavement in particular (Frantz et al. in Pastor Psychol 44(3):151-163, 1996) and has been shown to effect college student reactions to stress in general (Merrill et al. in Mental Health, Religion & Culture 12(5):501-511, 2009). The RCOPE (Pargament et al. in J Clin Psychol 56(4):519-543, 2000, J Health Psychol 9:713-730, 2004) is a frequently used measure of religious coping, but has not been evaluated with a bereaved undergraduate population. Given that emerging adulthood is a critical developmental phase of religious identity (Fowler. in New Directions for Child Development 3(52):27-45, 1991), the current study examined the factor structure of the RCOPE within a sample of bereaved college students. An exploratory factor analysis was performed, which approximated the factor structure proposed by Pargament et al. (J Clin Psychol 56(4):519-543, 2000). However, a high correlation between the positive and negative religious coping subscales (r = 0.71) detracted from the predictive utility of Pargament et al.'s (2000) two overarching subscales. Therefore, an exploratory factor analysis with an orthogonal rotation was used to identify two uncorrelated subscales (adaptive religious coping and maladaptive religious coping). This new two-factor, 39-item version of the RCOPE was found to demonstrate good internal consistency (a > 0.8) as well as convergent and discriminant validity. The interaction between religious coping strategies and core beliefs about the predictability of the world is explored, and directions for future research and clinical practice are suggested.